2011
DOI: 10.1007/s00345-011-0673-4
|View full text |Cite
|
Sign up to set email alerts
|

Sequential therapies with sorafenib and sunitinib in advanced or metastatic renal cell carcinoma

Abstract: This study endorses the notion of a clinical benefit of the sequential use of sorafenib and sunitinib and supports observations from previous studies. In terms of the optimal succession of the two TKIs, the study does not allow a definite answer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 10 publications
1
9
0
1
Order By: Relevance
“…In a phase 3 study of sorafenib in pretreated (mostly with cytokines) mRCC patients, the ORR was low (2% by independent radiologic review) with no CRs [2]. Similarly, in various studies of sorafenib in patients who had previously received VEGF-targeted therapies, response rates have been low (0%–9.6%) with a modest median PFS or time-to-progression (around 4 months) [37,39-43]. Although it is not possible to discern the relative contributions of IL-21 and sorafenib to the overall antitumor activity in this single-arm study, it is plausible that IL-21 contributed to the activity of the combination, given the modest ORR and PFS generally seen with sorafenib monotherapy in mRCC patients who have previously been treated (especially with VEGF-targeted therapies).…”
Section: Discussionmentioning
confidence: 99%
“…In a phase 3 study of sorafenib in pretreated (mostly with cytokines) mRCC patients, the ORR was low (2% by independent radiologic review) with no CRs [2]. Similarly, in various studies of sorafenib in patients who had previously received VEGF-targeted therapies, response rates have been low (0%–9.6%) with a modest median PFS or time-to-progression (around 4 months) [37,39-43]. Although it is not possible to discern the relative contributions of IL-21 and sorafenib to the overall antitumor activity in this single-arm study, it is plausible that IL-21 contributed to the activity of the combination, given the modest ORR and PFS generally seen with sorafenib monotherapy in mRCC patients who have previously been treated (especially with VEGF-targeted therapies).…”
Section: Discussionmentioning
confidence: 99%
“…Herrmann et al [17] reported 54 patients in So-Su and 33 patients in Su-So group. The median PFS were 12.1 vs 15.4 months and the median OS were 28.8 vs 28.9 months.…”
Section: Resultsmentioning
confidence: 99%
“…Parts of recent retrospective studies have suggested that sorafenib followed by sunitinib (So-Su) was optimal to sunitinib followed by sorafenib (Su-So) in progression-free survival and overall survival [812]. Nevertheless, a recent randomized controlled trial SWITCH [13] and several retrospective studies [1417] argued that So-Su and Su-So offer similar clinical efficacy in mRCC, with no statistically differences.…”
Section: Introductionmentioning
confidence: 99%
“…Wie demgegenüber unter Berücksichtigung retrospektiver Serien unter Einschluss von >700 Patienten offensichtlich wird, entfalten Sorafenib und Sunitinib auch in der Zweitlinie nach Therapieversagen gegenüber einer TKIbasierten Erstlinienbehandlung Wirksamkeit [9,10,11,12,13].…”
Section: Systemtherapie In Der Zweitlinie Sequenzund Kombinationstheunclassified